Vzgoja kultiviranega bralca kot najpomembnejši cilj pouka književnosti v gimnaziji - Jožef-Beg, Jožica (Jezik in slovstvo, 2015)
The most important goal of literature classes in grammar schools is the education of cultivated readers. This goal justifies the implementation of a systemic literary didactic paradigm, while also overlapping with European trends in literature didactics. The thesis in the present article is illustrated first with an example from the Curriculum for Slovenian Language (2008), followed by an example from the document The Literary Framework for Teachers in Secondary Education (2012), and finally with findings from research conducted to determine how students' own experience with reading literature/fiction and with literature classes influences the way they perform various tasks in their lives.
Keywords: didaktika književnosti; sistemska didaktika; branje; kultivirani bralec; literarna zmožnost; gimnazije